Computed tomography-guided percutaneous cryoablation of T1b renal tumors: safety, functional and oncological outcomes. (1st January 2019) - Grange, Rémi; Tradi, Farouk; Izaaryene, Jean; Daidj, Nassima; Brunelle, Serge; Walz, Jochen; Gravis, Gwenaëlle; Piana, Gilles
Abstract: Purpose: To evaluate the safety, functional and oncological outcomes associated with percutaneous cryoablation of stage T1b renal cell carcinoma (RCC). Materials and methods: Institutional database was reviewed to identify patients treated by percutaneous CT-guidance cryoablation between 2013 and 2018 for biopsy-proven RCC tumors measuring 4.1–7.0 cm. The main outcome parameters analyzed were primary and secondary technique efficacy, progression-free survival (PFS), cancer-specific survival (CSS), loss of estimated glomerular filtration rate (eGFR) and complications. PFS and CSS were estimated by the Kaplan–Meier method. Complications were graded by the Clavien–Dindo system. Results: Twenty-three consecutive patients were included (mean tumor diameter: 45.6 ± 6.2 mm; mean RENAL score: 8.1 ± 1.8). The technical success rate was 95.7%. Primary and secondary technique efficacy rates were 86.3 and 100%, respectively. Three patients found to have incomplete ablations at 3 months were successfully treated by repeat cryoablation. Median duration follow-up was 11 months (range: 3-33). Imaging showed PFS to be 85.7% at 6 months, 66.7% at 12 months and 66.7% at 24 months. One patient with a local recurrence at 12 months was treated by radical nephrectomy. One patient died from progression of disease within 12 months. One patient reported a complication grade ≥ II (4.3%). Mean eGFR loss was 4.4 ± 8.5 ml/min/1.73m 2, which was significantly higher among those treated for central tumors ( p  < .05). Conclusion: Cryoablation for stage T1b renal tumors is technically feasible, with favorable oncological and perioperative outcomes. Longer-term studies are needed to verify our findings.